(untitled) (Journal of Hama University, 2019)
This study was conducted to investigate the prevalence of staphylococcus aureus in milk collection tanks in the markets of Hama Governorate, where 300 milk samples were collected from milk collection tanks in the local markets from different regions of Hama governorate for a year during the period from May 2017 to May 2018.The study reported that the absolute frequency of total positive samples were 146 in both regions down town and rural regions of Hama with prevalence of 48.66% and that infection was higher in the countryside of Hama governorate with a prevalence of 59.30% compared to Hama City 27.34%. The highest prevalence of staphylococcus aureus was 74.32% in dirty tanks compared to clean tanks 23.68%. tanks made of Metal material had reported higher prevalence than the reservoirs made of Plastic material with a prevalence of 70.14% and 42.48%,respectively.